Model Transmisi Intergenerasi Perikanan Tangkap di Pesisir Selatan - Nelonda, Selli; A Kinseng, Rilus; Sapanli, Kastana; Novindra, Novindra (Jurnal Ecogen, 2025)
This research aims to identify the determining factors for the transmission of fishing between generations and analyze the intergenerational model with the variable parental support in creating sustainable livelihood activities in coastal areas. This research uses a seemingly unrelated bivariate probit regression model and multinomial logistic regression with 270 samples. The results show that the intergenerational transmission of fishing work depends on the father's hopes and also the child's wishes, while the father's hopes of wanting his child to become a fisherman like himself (which is the cause of endogeneity) depends on the child's liking for the sea, the education of household head, the experience of household head. steps, the conditions of fishing business and community participation. From the multinomial logistic regression model, the results show that variables that describe economic and social conditions play an important role in the decision to occur intergenerational transmission.